# Use the quadratic formula to solve the equation. -2x^{2} - 5x + 5 = 0

**Solution:**

The standard form of a quadratic equation is ax^{2} + bx + c = 0

The formula used to solve it is

x = [-b ± √b^{2} - 4ac]/ 2a

The given equation is -2x^{2} - 5x + 5 = 0

Here a = -2, b = -5, c = 5

Substituting it in the quadratic formula

x = [-(-5) ± √(-5)^{2} - 4(-2)(5)]/ 2(-2)

By further calculation

x = [5 ± √25 + 40]/ (-4)

x = [5 ± √65]/ (-4)

So we get

x = -(5 + √65)/4 or x = -(5 - √65)/4

x = (-5 - √65)/4 or x = (-5 + √65)/4

Therefore, the solution is x = (-5 - √65)/4 or x = (-5 + √65)/4.

## Use the quadratic formula to solve the equation. -2x^{2} - 5x + 5 = 0

**Summary:**

Using the quadratic formula the solution of -2x^{2} - 5x + 5 = 0 is x = (-5 - √65)/4 or x = (-5 + √65)/4.

Math worksheets and

visual curriculum

visual curriculum